Balanced Scorecard: an empirical study of small and medium size enterprises - Machado, Maria João Cardoso Vieira (Review of Business Management, 2013)
Theory attributes advantages to the Balanced Scorecard as a performance evaluation method, when compared to exclusively financial measures. This study aims at analyzing Balanced Scorecard use and awareness rates amongst small and medium Portuguese industrial companies, researching factors that explain why the method is not familiar to all companies. Interviews were carried out with professionals in charge of management accounting in 58 industrial companies in eleven Portuguese districts. Evidence gathered allow us to conclude that very few enterprises use the Balanced Scorecard, and that most of the professionals interviewed are unaware of it. Research on explanatory factors allow us to conclude that awareness about this method depends on the individual characteristics of those in charge of management accounting, such as education and age; and on company characteristics, such as size.